Pedagogy for addressing emotional subordination among women workers. - Chan , Lean Heng (1996)
Conscientisation of women workers tend to focus on their material-objective conditions. Consciousness-raising about their structural oppression, that is, class exploitation and gender subordination are emphasised. However, their personal experiences and feelings are rarely taaken on board. The more subjective commonalities of unspoken thoughts and repressed feelings, especially the emotional implications of subordination, tend to be overlooked.